Communication Strategy of the General Election Commission as a Source of Information and Socialization of Legal Products in General Election - Yulianti Yulianti; Andi Vita Sukmarini; Syamsu Rizal (Journal La Bisecoman, 2024)
The aim of the research is to determine the KPU's communication strategy as a source of information and dissemination of legal products through the KPU's JDIH website, and to determine the factors that support and hinder the KPU's communication strategy. The research was carried out at the Makassar City KPU Office. This type of research uses a qualitative approach, with informants consisting of 6 (six) people. Data collection techniques consist of observation, interview guidelines and documentation. The data analysis technique uses qualitative analysis with three stages, namely data reduction, data presentation, data verification and conclusion drawing. The results of the research found that the KPU's communication strategy had been implemented as a source of information and socialization of legal products through the JDIH KPU website in accordance with the formation of a team in publishing regulations related to regional head elections on the JDIH KPU website, creating socialization materials, creating legal content to increase public knowledge about head elections. regions, publish on social media as a form of communication for target groups and facilitate access to social media channels for people who need information on regional head elections. Communication targets and choice of communication media are factors that support the KPU's communication strategy through the KPU's JDIH website. Meanwhile, assessing the purpose of the communication message and the role of the communicator is a determining factor in implementing the KPU's communication strategy.